The Mithralog EC-7072 Induces Chronic Lymphocytic Leukemia Cell Death by Targeting Tonic B-Cell Receptor Signaling - Lorenzo-Herrero, Seila; Sordo-Bahamonde, Christian; Bretones, Gabriel; Payer, Ángel R.; González-Rodríguez, Ana P.; González-García, Esther; Pérez-Escuredo, Jhudit; Villa-Álvarez, Mónica; Núñez, Luz-Elena; Morís, Francisco; Gonzalez, Segundo; López-Soto, Alejandro (Frontiers in Immunology, 2019)
B-cell receptor (BCR)-dependent signaling is central for leukemia B-cell homeostasis, as underscored by the promising clinical results obtained in patients with chronic lymphocytic leukemia (CLL) treated with novel agents targeting components of this pathway. Herein, we demonstrate that the mithralog EC-7072 displays high ex vivo cytotoxic activity against leukemia cells from CLL patients independently from high-risk prognostic markers and IGHV mutational status. EC-7072 was significantly less toxic against T cells and NK cells and did not alter the production of the immune effector molecules IFN-γ and perforin. EC-7072 directly triggered caspase-3-dependent CLL cell apoptosis, which was not abrogated by microenvironment-derived factors that sustain leukemia cell survival. RNA-sequencing analyses revealed a dramatic EC-7072-driven reprograming of the transcriptome of CLL cells, including a wide downregulation of multiple components and targets of the BCR signaling pathway. Accordingly, we found decreased levels of phosphorylated signaling mediators downstream of the BCR. Crosslinking-mediated BCR activation antagonized CLL cell death triggered by EC-7072, increased the phosphorylation levels of the abovementioned signaling components and upregulated BCL2 expression, suggesting that the mithralog disrupts CLL cell viability by targeting the BCR signaling axis at multiple levels. EC-7072 exerted similar or higher antileukemic activity than that of several available CLL therapies and displayed additive or synergistic interaction with these drugs in killing CLL cells. Overall, our findings provide rationale for future investigation to test whether EC-7072 may be a potential therapeutic option for patients with CLL and other B-cell malignancies.